Influence of consequences of anti-pandemic measures in connection withthe spread of coronavirus Covid-19 in the Czech Republicon selected body composition and performance parameters of children of younger school age - Hnízdil, Jan; Vojtíková, Lenka; Heidler, Josef; Škopek, Martin; Havel, Zdeněk (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. During the global COVID-19 pandemic, there has been a long-term and unprecedented reduction in physical activities. Aim of Study. The objective of the work was to describe specific changes in performance and body composition after long-term restrictions on mobility due to the COVID-19 pandemic in the group of young school children in the Czech Republic, which experienced one of the longest periods of closed schools and therefore restricted sports and leisure activities in the world. Material and Methods. This was a longitudinal study on an identical group of first-grade students (n = 52). The level of physical performance was repeatedly tested during the normal regime without any restrictions and after their return to school. The conducted test (standing long jump, shuttle run, sit and reach, sit-up test, endurance run) included also anthropometric measurements (weight, height, body fat content). Results. There was an increase in body fat by 64.23% (MD = 16.65 ± 2.73 cm; d = 0.85), increase in BMI values by 10.91% (MD = 1.77 ± 0.19 kg·m–1; d = 1.29), as well as a significant decrease in endurance running by 14.6% (MD = 58.56 ± 9.32 s; d = 0.71) and in the flexibility test (sit and reach) by 250% (MD = 6.04 ± 0.75 cm; d = 1.12). For standing long jump and shuttle run the post-lockdown testing showed performance to improve in absolute terms, with children remaining in the given categories compared to the norms, usually around the population average of the given category. In the sit up test the performance scores did not change, an non-significant improvement of two exercises was recorded, but when comparing average performance results with the norms the performance deteriorated. Conclusions. The long-term restrictions on the normal exercise regime had a devastating effect on key components of performance and health-oriented fitness.
Keywords: children; COVID-19; body composition; health related fitness